Empathy Among Orthopaedic Surgery Trainees. Issue 3 (July 2021) - Sabharwal, Samir; Lin, Carol; Weistroffer, Joseph K.; LaPorte, Dawn M.; Ponce, Brent; Van Heest, Ann; Juliano, Paul; Grabowski, Greg; Wilson, Robert; Scannell, Brian; Carr, Charles; Muchow, Ryan; et al.
Abstract : Background: It has been postulated that the process of—and stresses associated with—medical training may cause a loss of empathy among trainees. Because empathy is considered an important value for clinicians and may even be associated with better patient outcomes, we assessed the empathy of orthopaedic surgery trainees and identified factors associated with empathy. Methods: Between June and September 2020, an anonymous survey was distributed electronically to trainees in 23 Accreditation Council for Graduate Medical Education-accredited orthopaedic surgery residency programs via the Collaborative Orthopaedic Educational Research Group. The survey comprised the validated Short-Form 8-Item Empathy Quotient (EQ-8) questionnaire—scored on a scale of 0, least empathetic, to 16, most empathetic—and single-item measure of emotional exhaustion and depersonalization derived from the Maslach Burnout Index—scored using a frequency scale. In total, 438 of 605 (72%) trainees completed the survey. The scores were compared via one-way analysis of variance, with Bonferroni correction and Tukey post-hoc testing, α = 0.05. Results: The mean (±SD) EQ-8 score among respondents was 11.3 ± 3.3. Women scored significantly higher (mean, 12.2 ± 2.8) than men (mean, 11.2 ± 3.3) (p = 0.02). Mean scores were significantly higher for trainees planning on a career in academic medicine (12.0 ± 2.9) than those intending to pursue private practice (10.9 ± 3.3) or those with a military commitment (10.4 ± 3.4) (p = 0.01). An inverse relationship was found between EQ-8 scores and single-item Maslach Burnout Index measures in depersonalization and emotional exhaustion (both, p < 0.01). No significant differences were found in EQ-8 scores across postgraduate year, program location, primary training setting, intended fellowship, relationship status, or whether they reported having children. Conclusions: We found no association between postgraduate year and EQ-8 score. Women and those intending to pursue a career in academic medicine had significantly higher levels of empathy. A significant inverse relationship was found between burnout and empathy. Respondents with higher levels of emotional exhaustion and depersonalization had lower levels of empathy.